PERENCANAAN BANGUNAN PEMECAH GELOMBANG TERENDAM (SUBMERGED BREAKWATER) DENGAN BAHAN BATU BUATAN (DOLOS) DI PANTAI MASCETI, KABUPATEN GIANYAR - I Gusti Agung Angga Nuryana; I Gusti Agung Putu Eryani; Dewa Ayu Nyoman Sriastuti (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
Masceti beach is one of beach area in Gianyar Regency has erosion 2.006 km. Selection of the type of building breakwaters in terms of aesthetic aspects without reducing the beauty and sanctity of the temple, then selected submerged breakwaters with artificial stone materials (dolos). The use of artificial stone materials (dolos) is used considering the previous building that has not been too effective and has begun to break because it is not strong to withstand the onslaught of waves that hit the area. Result of analysis shown heigh of submerged break water is 3.2 m, 1st layer stone weight is 1 ton, 2nd layer stone weight is 61 kg, 3rd layer stone weight is 3 kg, top wide is 2.652 m, 1st layer width is 1.268 m, 2nd layer width is 0.588, foot width is 0.8 m, foot wide is 1.14 m, foot stone weight is 44 kg. Budget plan for construct two submerged breakwater are IDR 4,872,332,000.00. Keyword: erosion, wave, submerged, breakwater